The integrated framework of cloud computing implementation in higher education institution: a review of literature - K., Rahimah; N., Aziati (American Scientific Publishers, 2017)
Cloud computing has viewed as one of the most discussed issues that promise to modernize traditional computing by providing visualized resources as a service over the internet. To stable in cloud computing acquisition requires an organization to address many of the same concerns they face in implementing an Information Technology (IT) service. This study encompasses the factors that affect the decision of cloud computing implementation in the management of various industries focuses on Software as a service (SaaS) platform. By synthesizing the literature from different sectors, this paper proposed a conceptual framework of a key driver of cloud computing implementation for Higher Education Institutions (HEIs). This conceptual framework extracted from the analysis of the Technology, Organization and Environment (TOE) framework and integrate with Diffusion of Innovation (DOI) theory. The four dimensions, particularly technology, organization, external environment and environmental sustainability, would be highlighted which could be used as a guideline to accelerate the implementation process of the computing technology in Malaysia education industry. Thus, the paper offered, would contribute cloud computing organization users and service provider with a better understanding and guidelines of cloud computing implementation characteristics with relevant perception on current services.